Are Strengths the Solution? An Exploration of the Relationships among Teacher-rated Strengths, Classroom Behaviour, and Academic Achievement of Young Students - Whitley, Jessica; Rawana, Edward; Pye, Melissa; Brownlee, Keith (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2010)
Strength-based approaches are being increasingly validated for use in clinical settings with children and youth. However, the role that strengths play in educational settings with typically-achieving students has yet to be examined. The present study explored the relationship among strengths, classroom behaviour, and academic achievement for a sample of 54 students in Grades 1 and 2. Results showed that teachers rated female students as having more strengths than male students. For both sexes, academic achievement was most highly related to strengths in School Functioning and prosocial behaviour. Strengths in Peer Relationships were significantly related to achievement only for male students. Discussion of these findings, as well as implications for practice are presented.